Variation in leaf cutin content and chemical composition along one annual cycle in the Mediterranean Cork Oak (Quercus suber L.) - Simões, Rita (2023)
Plant leaves have one important protection barrier made up by a cuticle that covers their external surface and builds up a continuous extracellular, mostly hydrophobic, membrane on the epidermis that provides protection from biotic or abiotic stresses, namely from climatic harsh conditions, e.g., by limiting water loss and in heat insulation [1,2]. The cuticle includes a polymeric cutin matrix and cuticular waxes, linked to the epidermal cell wall by polysaccharides, also considered part of the cuticle as a cutin–polysaccharide matrix. Cutin is a polyester formed predominantly by cross-linking through ester bonds of C16 and C18 hydroxy fatty acids and glycerol, while cuticular waxes comprise very long-chain fatty acids and derivatives, alcohols, and alkanes as well as terpenes, sterols, and aromatics, and are soluble in non-polar solvents [3–6]. Cuticular waxes are located in the cuticle within the cutin matrix as an intracuticular layer, and on the outer surface of the cutin as an epicuticular layer [3]. Some cuticles also contain a resistant aliphatic polymer that is not depolymerized by ester-bond hydrolysis, the cutan, that has only a small proportion of aromatic moieties [7,8].